KESEPAKATAN UNIVERSAL ANTI-KEKERASAN DALAM KITAB SUCI AGAMA-AGAMA - Siti Khotijah; Mulyazir Mulyazir; Nila Rohmatuz Zahrok (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Issues of violence are often juxtaposed with religion; every religion seems to be inseparable from the dogma of violence. Ironically, the message of peace and non-violence in the holy books of religions tends to be ignored. This article does not aim to find differences but rather similarities as a reflection of comparative studies between religions to open new perspectives. This research is qualitative research with a comparative descriptive analysis method. Two fundamental questions in this research are how the scriptures of the world's largest religions (Judaism, Christianity, Islam, Hinduism, and Buddhism) speak about non-violence and worldviews related to inter-religious violence. The term violence in the scriptures of the heavenly religions (Judaism, Christianity, and Islam) is still present today, either in the form of God's encouragement and command or as a consequence of an event, while in the earthly religions (Hinduism and Buddhism) the term violence is not found. Despite this, radical and fundamentalist groups who claim their actions as legal defense according to religion still occur frequently; if this is true, acts of religious terror violence should not occur in earthly religions because there is no affirmation in their holy books. Therefore, this research agrees with Mark Juergensmeyer's opinion that the study of religious terror must be raised together with the context in the form of historical situations, social locations, and worldviews related to violence because the violence contained in the holy book has its own time and event limitations.